Aggravation of dysphagia after surgical removal of anterior cervical osteophytes: a case report - Young-In Go; Gi-Wook Kim; Yu-Hui Won; Sung-Hee Park; Myoung-Hwan Ko; Jeong-Hwan Seo; Da-Sol Kim (Journal of International Medical Research, 2022)
Dysphagia induced by anterior cervical osteophytes (ACOs) is frequently reported in older individuals. Surgical resection of ACOs is considered when conservative treatment fails, but its effectiveness is controversial owing to side effects after surgery. We present the case of a 78-year-old man who complained of progressive dysphagia that started 10 months previously. A videofluoroscopic swallow study (VFSS) showed prominent ACOs along C2–C6, which translocated the upper hypopharynx anteriorly, impinging the lumen and impairing epiglottic folding and laryngeal closure. Aspiration of a soft diet was observed. Despite conservative therapy, the symptoms persisted, and ACO resection surgery was performed. Unexpectedly, the patient’s dysphagia worsened immediately post-surgery. A VFSS on postoperative day (POD) 2 showed improvement in epiglottic folding. However, prevertebral soft tissue swelling and dysfunction of opening of the upper esophageal sphincter newly arose. Laryngeal aspiration was observed during 5 cc and a large amount of liquid swallowing trials. The patient was provided a modified diet and rehabilitative dysphagia therapy. A VFSS on PODs 6 and 14 showed a gradual improvement in the prevertebral soft tissue swelling. This report suggests that a serial VFSS is effective for evaluating the different mechanisms of dysphagia and for devising an appropriate treatment plan.